Waste disposal into water resources: Ethical evaluation from the Islamic point of view - Mahmod, Safa Senan; Kabbashi, Nassereldeen Ahmed (2013)
Recently, the need to protect and sustain the water resources has attracted many researchers’ attention on which every living thing depends on. Consequently, consumption of polluted water puts lives (human, animal, plants) at risk because water has no substitute. Water is a renewable natural resource. Due to ever increasing industrialization and urbanization, this precious resource is continuously under stress. One of the many ways in which water can get polluted is through waste discharge from industries like mining and construction, food processing, chemicals and radioactive wastes from power generating industries, domestic and agricultural wastes. These pollutants cause changes in the physical, chemical or biological properties of water making it contaminated; that is thought to be the cause of many illnesses and the spread of diseases through drinking. Islam has urged humanity to be kind to nature and not to abuse the trust and responsibility given to Mankind. There are two primary sources defining Islam: The Quran and the Hadith, and both sources emphasize the accountability and responsibility of man toward the rest of creation. Based on these two sources, this paper will discuss the role of man towards the environment, especially its water resources.